KONSTRUKSI MULTIDIMENSIONAL PADA TEATER KEPAHLAWANAN SULTAN HASANUDDIN (AYAM JANTAN DARI TIMUR): SEBUAH TINJAUAN ANALISIS SEMIOTIKA PADA PERTUNJUKAN TEATER - Saputra, Andi Taslim; Suyudi, Muhammad (Universitas Negeri makassar, 2025)
This research aims to explore the semiotic markers created in the performance of Sultan Hasanuddin (The Rooster from the East). This performance becomes a medium that not only entertains but also produces symbols from multidimensional constructs in theater performances. In this research, a qualitative research method is used with an in-depth study of the performance facts and field facts constructively. The research findings reveal two aspects related to the creative process and multidimensional construction. In the creative process, it is described in the context of ideas, research, and the concretization of performance. In the context of multidimensional construction through the triadic semiotic description of icon, index, and symbol. The Sultan Hasanuddin performance (Rooster from the East) makes us feel as if there is an audio and visual space that communicates with each other and transcends boundaries. This is what is later referred to as a multidimensional construction in the Sultan Hasanuddin Theater performance (Rooster from the East).